(untitled) (World Science, 2021)
The occurrence of postoperative cognitive dysfunction is a negative consequence of vascular endothelial dysfunction in patients with grade I-II obesity with appropriate metabolic shifts and comorbid background, which increases the duration of treatment and worsens the prognosis in patients with acute surgical pathology. It is important to add endothelioprotectors to the intensive care unit. L-arginine hydrochloride has been shown to be pathogenetically justified as a prophylaxis for an increase in the level of antigens to von Willebrand factor in the blood of obese patients with acute surgical pathology. Administration of this substance before and during surgery is likely to improve mental performance in the postoperative period in patients with elevated body mass index, who underwent emergency cholecystectomy.